Synthesis of microcapsules for carbon capture via needle-based droplet microfluidics - Yew, Maxine; Ren, Yong; Koh, Kai Seng; Sun, Chenggong; Snape, Colin; Yan, Yuying (Elsevier, 2019)
“Off-the-shelf” devices have attracted much consideration lately, especially in emulsions production in droplet-based microfluidics. While many simple and cost-effective designs have been proposed and demonstrated, the functionability of these purported simple devices has been questioned, especially in emulsions generation for commercial scale. In this work, a simple needle-based device was used in the production of functional core-shell microcapsules of uniform sizes, typically in the range of 600 to 720 µm, and shell thickness of 20 to 110 µm, and C.V of 0.97 to 3.0%. These core-shell microcapsules are a new form of carbon capture materials, with carbon solvent encapsulated in thin polymeric shell. The microcapsules synthesized were subjected to absorption-desorption tests. This work has successfully demonstrated the use of off-the-shelf microdevice and its reliability for the production of functional microcapsules.